Fampridine Prolonged Release Improves Walking Ability and Balance in Patients with Multiple Sclerosis - Vinall, Phil (MD Conference Express, 2014)
Treatment with prolonged-release fampridine results in sustained, clinically meaningful improvement in walking ability and balance in patients with multiple sclerosis (MS). This article presents the results of Exploratory Study to Assess the Effect of Fampridine on Walking Ability and Balance in Patients With Multiple Sclerosis (MOBILE; NCT01597297), an exploratory, phase 2, randomized, double-blinded, placebo-controlled trial.